Interpreting societal culture value dimensions - Peterson, Mark F; Barreto, Tais S (Journal of International Business Studies, 2018)
Societal cultural value dimension scholarship can both learn from and inform the family of interrelated approaches to culture research in IB that appear in recent commentaries. It can exchange insights about societal values and meaning systems with neo-institutional and institutional logics research. It can also exchange insights with dual-processing cognition theories that are used to understand individuals in an international context by treating societal culture values and institutional characteristics as essential to interpreting personal values and attitudes. Rather than merging them, integrating culture-related specialties by exchanging insights can promote the further development of research in each of these societal and individual level fields.